Pola Konsumsi Makanan Mempengaruhi Kadar Vitamin D dan Kualitas Hidup Anak pada Masa Growth Spurt Kedua: Food Consumption Pattern Affects Vitamin D Levels and Quality of Life in Children during the Second Growth Spurt Period - Atina Hussaana; Siti Thomas Zulaikhah; Ratnawati Ratnawati (Universitas Airlangga, 2023)
Background: The second growth spurt period needs attention related to the intake of macro-nutrients and micro-nutrients, including vitamin D. So far, the evaluation of vitamin D has received less attention if indoor activity patterns exacerbate it and imbalanced food consumption patterns, it raises concern to trigger vitamin D deficiency and affect the children growth, development and quality of life. Objectives: To determine the relationship between children's consumption patterns on vitamin D levels, weight, height, and quality of life of children aged 10-12 years. Methods: Observational research with the cross-sectional design was conducted on 40 children 10-14 years old without physical disability from Pondok Kun Assalam Sentono and Madrasah Ibtidaiyah At-Taqwa Semarang, Indonesia. All subjects were measured consumption patterns using the Food Frequency Questionnaire (FFQ), blood levels of vitamin D, height, weight, leg length, and quality of life measured using the Pediatric Quality of Life Inventory (PedsQL). Results: The results showed that out of 40 subjects, only 3 (7.5%) children had sufficient vitamin D levels (≥30 µg/mL). There was a significant relationship between food consumption patterns and blood vitamin D levels (p<0.01), height, weight, leg length, and quality of life (p<0.05). The Spearman correlation coefficient values, respectively, between food consumption patterns and blood vitamin D levels, height, weight, leg length, and quality of life were; 0.404; 0.290; 0.369; 0.380; 0.321. Conclusions: The food consumption patterns of children in the second growth spurt period need to be considered because they are associated with vitamin D levels, height, weight, and quality of life.